2003
DOI: 10.1097/00043426-200308000-00011
|View full text |Cite
|
Sign up to set email alerts
|

Fetal Rhabdomyomatous Nephroblastoma: Report of 14 Cases Confirming Chemotherapy Resistance

Abstract: The authors retrospectively reviewed their experience with 14 cases of fetal rhabdomyomatous nephroblastoma (15.6% of all renal tumors seen in the 1984-1998 period), analyzing the diagnostic and treatment approach as well outcome. Mean age at presentation was 27 months; 10 (71%) patients were younger than 36 months (5 of these were less than 12 months) at diagnosis. Three patients had bilateral tumors. One case was extrarenal. Nine patients received preoperative chemotherapy after fine-needle aspiration biopsy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 11 publications
0
12
0
Order By: Relevance
“…It may also be possible to explain the histologic features of the lung nodules as part of the spectrum of the fetal rhabdomyomatous variant of WT (FRWT), which has been described in several recent reports 11,12. NWTS‐4 reported 35 cases in 2,077 patients (1.8%) of this rare variant.…”
Section: Discussionmentioning
confidence: 99%
“…It may also be possible to explain the histologic features of the lung nodules as part of the spectrum of the fetal rhabdomyomatous variant of WT (FRWT), which has been described in several recent reports 11,12. NWTS‐4 reported 35 cases in 2,077 patients (1.8%) of this rare variant.…”
Section: Discussionmentioning
confidence: 99%
“…Skeletal muscle in various stages of differentiation, including rhabdomyoblasts ( Figure 1B, C) represents the most common divergent line of differentiation [23]. Rare cases of WT showing diffuse and predominant rhabdomyoblastic differentiation have been reported in the literature under the descriptive term of fetal rhabdomyomatous nephroblastoma [24]. This exceedingly rare variant of Wilms' tumour shows little or no response to preoperative chemotherapy and is associated with a generally favourable outcome in most of all unilateral cases when treated by surgery.…”
Section: Nephroblastoma (Wilms Tumor)mentioning
confidence: 99%
“…1). 10,11 ANAPLASIA Several large studies have demonstrated that the presence of anaplasia in WT is associated with lack of response to chemotherapy with an adverse outcome. 2).…”
Section: Pathologic Featuresmentioning
confidence: 99%